Cleaning and shaping curved root canals: Mtwo® vs ProTaper® instruments, a lab comparison - Kuzekanani Maryam; Walsh Laurence; Yousefi Mohammad (Wolters Kluwer Medknow Publications, 2009)
Objectives: The purpose of this study was to compare root canal preparation in curved canals in molar teeth with the rotary NiTi Mtwo and ProTaper systems in terms of canal shape and smear layer. Materials and Methods: Mesiobuccal canals of 60 molar teeth with angles of curvature between 25 and 35 degrees were prepared with a torque controlled low speed engine; 30 canals for each system. Each individual instrument was used to prepare four root canals and the time required for preparation was recorded. Standardized radiographs were taken before and following instrumentation and used to determine changes in canal curvature. Results: There was no significant difference in preparation time between the two systems. No instruments separated during use. The Mtwo system gave a statistically smaller change in canal curvature and thus was better for maintaining the original shape of the root canal, with less transportation (P less than 0.05). The greatest difference was seen for maxillary molar teeth. When prepared root canals were examined by SEM there was no difference between the two systems at the coronal, middle or apical thirds. Conclusion: Overall, the results of this study suggest that Mtwo instruments are preferable for situations where canals are curved, particularly for maxillary molars.